Retificador Boost Interleaved com correção do fator de potência para um carregador de baterias de um veículo elétrico Fórmula SAE - Batista, Daniel Souza (2023)
Battery-dependent systems are increasingly becoming present in people's daily lives through numerous applications, such as electric vehicles and energy storage systems for renewable sources. Typically, battery chargers are composed of two energy conversion stages, namely: the AC-DC conversion stage and the DC-DC conversion stage. This work aims to study the first stage of conversion of a battery charger, which is implemented by a Boost Interleaved rectifier with power factor correction. With Power factor correction, the battery charger provides high energy quality to the power grid, mitigating the problem of harmonic distortion present in traditional diode bridge rectifiers. Theoretical studies are presented for dimensioning the power and control stages of the rectifier. Finally, numerical simulation results are presented considering a rectifier operating in continuous conduction mode and with the following design specifications: input voltage of 220 V, input voltage frequency of 60 Hz, output voltage of 400 V, rated power of 5 kW, and switching frequency of 50 kHz.